Evaluation of corneal higher order aberrations in normal topographic patterns - Mirzajani, Ali (J Curr Ophthalmol, 2016)
PURPOSE: This study reports the characteristics of corneal higher order aberrations (HOAs) in eyes with normal topographic pattern using the Pentacam scheimpflug system. METHODS: In this prospective, observational, comparative study, 165 eyes of 97 patients separated into five groups based on corneal topographic patterns were enrolled. All eyes received a comprehensive ophthalmologic examination including corneal tomographic analysis with the Pentacam system. Keratometry, corneal cylinder, and corneal aberrometric data were recorded and analyzed. Root mean square values (RMS) were calculated for corneal HOAs up to the 6th order, total coma, total trefoil, total spherical aberration, total tetrafoil, and higher order astigmatism. Evaluation of these data to discriminate between the five groups was assessed using the analysis of variance test by Generalized Estimation Equation Linear Model. RESULTS: Corneal HOAs were found to be significantly higher for Asymmetric Bow Tie and Irregular groups than other groups (p = <0.001). RMS of total coma aberration ([Formula: see text] , [Formula: see text] , [Formula: see text] , [Formula: see text]) were significantly greater in the Asymmetric Bow Tie pattern than others, and RMS of total Spherical aberration ([Formula: see text] , [Formula: see text]) was significantly higher in the Irregular pattern than other groups (p = <0.001). The results of our study demonstrate that a tendency toward significant higher values of trefoil, tetrafoil, and higher order astigmatism in Irregular pattern (all p < 0.05). Significantly higher amounts of 3rd order RMS in Asymmetric Bow Tie group and 4th to 6th order RMS in Irregular pattern group were other outcomes of our study (p = <0.001). CONCLUSIONS: Based on results in this study, there were a good correlation between corneal topographic pattern and corneal HOAs in normal eyes. These results indicate that the corneal HOAs values are largely determined by the topographic patterns. A larger sample size would perhaps have been beneficial to yield in more accurate outcomes.